Automatic Carrier-to-Signal Power Ratio Control for Optical Transmitter - Li, Hongyu; Li, Xinghan; Huang, Chuanming; Cheng, Mengfan; Yang, Qi; Tang, Ming; Liu, Deming; Deng, Lei (Journal of lightwave technology, 2025)
The growing demand for short-to-medium reach fiber optics transmission systems has driven the exploration of self-coherent receiver schemes in recent years. The optical carrier-to-signal power ratio (CSPR) plays a crucial role in these applications; however, there have been no reports on automatic CSPR control (ACC) thus far. In this paper, we propose an optical ACC-based transmitter that can realize real-time, precise, and stable CSPR control for the first time. The proposed scheme comprises solely an optical IQ modulator (IQM) and an automatic bias controller (ABC). The regulation of CSPR for ACC-based transmitters is achieved through a redesigned automatic bias point control module utilizing dither-correlation detection, and a CSPR estimation method has been developed to enable long-term precise and stable closed-loop control of CSPR. The relationship between the bias point offset and the carrier power is derived in this study. The experimental results demonstrate that our scheme achieves a CSPR measurement accuracy of 0.43 dB. Moreover, the ACC-based optical transmitter enables precise and stable control of CSPR, ensuring fluctuations are maintained within a minimal range of 0.32 dB over a half-hour duration. The proposed ACC-based transmitter enables successful transmission of a 20 Gbaud 16 QAM signal over a distance of 50 km using standard single-mode fiber (SSMF) in the Kramers-Kronig (KK) receiver-based transmission system, achieving comparable performance to the traditional external optical carrier-assisted scheme.